Assessing bio-physical feedbacks in the shelf areas of Laptev Sea - Pefanis, Vasileios; Altenburg Soppa, Mariana; Loza, Svetlana; Hellmann, Sebastian; Janout, Markus; Rozanov, Vladimir; Dinter, Tilman; Bracher, Astrid (2018)
In the context of climate change and of thawing permafrost in Siberia, the freshwater and organic material supplied by rivers to the Arctic Ocean, may increase heavily in the future. Here, we investigate the effect of the variability of optically active water constituents on the heat budget of the Laptev Sea surface waters. As a first step, we simulate the radiative heating with coupled atmosphere-ocean radiative transfer modelling (RTM). By using satellite remote sensing retrievals of Coloured Dissolved Organic Matter (CDOM), Total Suspended Matter (TSM), Chlorophyll-a (Chla) and sea surface temperature data as input to the RTM simulations, we present the spatial distribution of potential radiative heating of Laptev Sea shelf areas. Additionally, an ocean biogeochemical model coupled to a general circulation model is used to simulate the dynamics of various constituents in response to Arctic Amplification and the feedback on surface heating and sea ice melting. Results suggest that high concentration of CDOM, TSM and Chla in Arctic waters increase the heating rate at the surface of the ocean and reduce the heat losses to the atmosphere during summer. The induced surface heating can result to higher ice melting rates with potential implications to upper ocean stratification and primary production.